A. C. Ewing - A Critical Survey of Ewing's Recent Work - Knox, John (Religious studies, 1975)
Is the existence of God a reasonable metaphysical hypothesis? So asks A. C. Ewing in his important posthumous work, Value and Reality. Thus the topic of the book is theistic religion, not in its entirety, but rather merely in its intellectual part. That it does have such a part, and further that it makes claims to objective truth in the field of metaphysics' (p. 24), is defended on the grounds (a) that a fictional story' about God has what religious or ethical impact it may have because, or at least mainly because, it is taken precisely not as fictional, but as expressing an objective theological truth; and (b) that a story, or an account, can constitute a good reason for one's acting in a certain way only if the account is, in fact, objectively true. Bearing on both points is Ewing's observation that emotion, at least except in pathological cases, requires some objective belief about the real, true or false, to support it for long, and if it exists without knowledge or rationally founded belief with which it is in agreement, it is to be condemned as irrational or unfitting, as it would be unfitting to rejoice at something disastrous or be angry with an inanimate thing' (p. 27). The claim is not, we are told, that religious statements are literal as distinguished from symbolic. The door would seem to be left open, in fact, to their all being symbolic. What is essential is that some of them symbolise distinctively metaphysical truths, or truths going beyond the realm of science' and throwing some light on the general nature of the real' (p. 30). We should indeed distinguish, Ewing notes, belief in' from belief that'. Yet the former is not possible without the latter. Unless I believe that God exists I cannot believe in God' (p. 28). So in Ewing's opinion, statements of metaphysics—if not concerning God, then at least concerning certain general aspects of reality—are most important for religion as a whole, and are, in being true, conceptually necessary to its validity, or to its fittingness'.